Prevalence of Newly Diagnosed Hypertension in Stroke Patients Presented to Tertiary Care Hospitals in Rawalpindi - Najma Fatima, Muhammad Salman, Husnain Hashim, Asma Ambreen, Tahir Mukhtar Sayed, Shahid Waheed (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Stroke is defined as the sudden onset of neurological deficits caused by vascular supply disruption to brain-specific region, contributing as a major factor for mortality and morbidity worldwide. Globally, approximately two-thirds cases of stroke are caused by hypertension as a major risk factor. The purpose of the current study was to determine the prevalence of stroke patients with newly diagnosed hypertension admitted to tertiary care hospital. Materials and Methods: This cross-sectional study was carried out on 205 stroke patients admitted to the Department of General Medicine, Benazir Bhutto Hospital and Holy Family Hospital, Rawalpindi from April 2021 to March 2022. Prior to study conduction, ethical approval was taken from the institute research and ethical committee. Written informed consent was obtained from each individual. All the participants underwent physical examination after using antihypertensive medication besides detailed history. Blood pressure was measured using standard mercury Sphygmomanometer. Patient having blood pressure ≥ 140/90 mm Hg was considered as hypertensive after measurement with difference of 10 minutes time span. SPSS version 25 was used for data analysis. Results: The overall mean age was 59.6 ± 8.5 years. Of the total 205 stroke patients, there were 140 (68.3%) males and 65 (31.7%) females. Out of 205 patients, 60.5% were rural and 39.5% were urban. The literacy rate was 63.9%. Family history of smoking, diabetes mellitus (DM), and hypertension (HTN) among study population were found in 83 (40.5%), 76 (37.1%), and 71 (34.4%) respectively. Based on computed tomography presentations, the prevalence of newly diagnosed hypertension (HTN) was 122 (59.5%). Out of 122 newly diagnosed hypertensive stroke patients, the incidence of ischemic stroke and hemorrhagic was 67 (54.9%) and 55 (45.1%) respectively. The mean value of diastolic and systolic blood pressure was 86.32 ± 12.62 and 125.59 ± 19.97 mm of Hg respectively. Conclusion: The present study concluded that the prevalence of newly diagnosed hypertension was found higher among stroke cases. Early diagnosis of hypertension by proper screening and effective treatment can reduce the mortality and morbidity caused by stroke and hypertension. Keywords: Hemorrhage, HTN, Ischemia, Stroke.